Improving the Usefulness of the Multidimensional Pain Inventory - Jeffrey M McKillop; Warren R Nielson (Pain Research and Management)
BACKGROUND: The Multidimensional Pain Inventory (MPI) is a reliable and valid self-report instrument that measures the impact of pain on an individual’s life, quality of social support and general activity. Criticism of the MPI has focused on this instrument’s internal structure and the stability of its classification taxonomy.